The inscription of the statue of Divus Commodus in Sopron - Szabó, Ádám (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The collection of the Liszt Ferenc Museum Sopron, contains, among other pieces, a fragment of a marble slab. The elegantly cut letters follow the writing style of the Antonine age, with their forms close to those of scriptura monumentalis. The formal features of the fragment, its thickness and frame breadth as well as its elaboration suggest, excluding the possibility of funerary or building contexts, that the slab was the front side of a statue base. The letters COM at the beginning of the first line can be restored to give the name Com[modus], while the fragmentary word FRAT in line 2 gives frat[er] or some of its inflected forms, if one considers the internal coherence of the two words and excludes similar but improbable variants.